Squalene Emulsion Manufacturing Process Scale-Up for Enhanced Global Pandemic Response - Tony Phan; Christian Devine; Erik D. Laursen; Adrian Simpson; Aaron Kahn; Amit P. Khandhar; Steven Mesite; Brad Besse; Ken J. Mabery; Elizabeth I. Flanagan; Christopher B. Fox (MDPI AG, 2020)
Squalene emulsions are among the most widely employed vaccine adjuvant formulations. Among the demonstrated benefits of squalene emulsions is the ability to enable vaccine antigen dose sparing, an important consideration for pandemic response. In order to increase pandemic response capabilities, it is desirable to scale up adjuvant manufacturing processes. We describe innovative process enhancements that enabled the scale-up of bulk stable squalene emulsion (SE) manufacturing capacity from a 3000- to 5,000,000-dose batch size. Manufacture of concentrated bulk along with the accompanying viscosity change in the continuous phase resulted in a ≥25-fold process efficiency enhancement. Process streamlining and implementation of single-use biocontainers resulted in reduced space requirements, fewer unit operations, and minimization of cleaning requirements. Emulsion physicochemical characteristics were measured by dynamic light scattering, laser diffraction, and HPLC with charged aerosol detection. The newly developed full-scale process was demonstrated by producing two 5,000,000-dose batches of bulk concentrated SE. A scale-up of adjuvant manufacturing capacity through process innovation enables more efficient production capabilities for pandemic response.